Traditional ecological knowledge (TEK) in selected heritage mosques of Malacca, Malaysia - Harun, Rosta; Othman, Fadhilah (IDOSI Publications, 2011)
The art of mosque architecture gives a way of understanding about the relationship between Islam and local people’s culture. This study aims to discover environmental philosophy of heritage mosques in Malacca with the main objective of the study is to uncover traditional ecological knowledge (TEK) elements in heritage mosques of Malacca to see how previous people communicate with environment through religious building. Qualitative approaches were used as methodology of this study. Five mosques were selected after literature analysis on available heritage mosques’ history and information. Selection was made based on the longest periods they had been established and moderate distance between each other to limit external influences onto TEK. The findings indicated that uncovered TEK from selected heritage mosques in Malacca consists of the ideas on hierarchy of nature, mosque symbolization of earth, som and sulur bayung, spiritual value of heritage mosque and carved coral reef summit. Most inspirations on mosque structure and design were taken from previous people observation upon the environment which they had translated creatively in several structures of the mosques. Nevertheless, the TEK of heritage mosques in Malacca still obey Islamic core value (aqidah).